Analisis Putusan MK No. 46/PUU-VIII/2010 tentang Status Anak Hasil Nikah Siri Perspektif Maqāsid Syarī’ah Imām Al-Syātibī - Rendy Dwi Hermanto (Institut Agama Islam Negeri (IAIN) Kediri, 2022)
The Constitutional Court's decision Number 46/PUU-VIII/2010 concerning the status of children born out of wedlock is a revolutionary decision made by the Constitutional Court. The decision stated that children born out of wedlock not only have a civil relationship with the mother and their mother's family, but also have a civil relationship with their biological father and biological father's family which can be proven based on the development of science and technology. The changes that occur in Article 43 paragraph (1) have implications for Islamic family law in Indonesia. The new law is interesting if reviewed using maqāṣid syarī'ah analysis with library research, with documentation data collection techniques, and uses two data sources, primary and secondary. The results showed that according to the maqāṣid syarī'ah analysis, the Constitutional Court's decision did not violate the the rules of syara', because it contained maṣlaḥah (goodness) and did not contain elements of ḍarar (damage) in the decision. This decision is also in line with the principles of maqāṣid syarī'ah, namely the principles of ḥifẓ al-dīn (protection of faith or religion), ḥifẓ al-nafs (protection of life), ḥifẓ al-‘aql (protection of intellect), ḥifẓ al-nasl (protection of lineage or ancestry) and ḥifẓ al-māl (protection of property or wealth). The implication of this decision is that children born out of wedlock have the same rights as children born from legal marriages, namely the right to lineage to their biological father, to earn a living, inheritance and equality before the law.